Kajian Kerawanan dan Kerentanan Banjir di Kecamatan Kota Kendal Kabupaten Kendal - Hisyam Noor Nugroho; Sri Rahayu (Teknik PWK (Perencanaan Wilayah Kota), 2019)
Kota Kendal sub-district according to Regional Regulation No. 20 of 2011 about Urban dan Regional Planning Kendal Regency in 2011-2031 was included in one of the flood-prone districts. The purpose of this study was to assess the level of hazard and vulnerability of flooding in Kota Kendal Subdistrict. The type of analysis carried out was AHP analysis, analysis of flood hazard and vulnerability using GIS software. Based on the results of the analysis of flood hazard, it is known that there are 3 levels of flood hazard, high, medium, and low. The high level located along the Kendal River. Middle level area is an area that is passed by the Kendal River, Buntu River, and Blorong River. Low flood level area in some areas in 7 subdistricts. Based on the results of the flood vulnerability analysis, there are 2 levels of flood vulnerability, middle, and low, including 12 sub-districts included in the middle vulnerability and 3 sub-districts included in the low vulnerability. In order to reduce the impact of flooding, it is expected that the local government can improve socialization of disaster response and early warning to residents who are at high and middle levels of hazard and vulnerability.